2000
DOI: 10.1029/2000wr900127
|View full text |Cite
|
Sign up to set email alerts
|

Importance of poroelastic coupling in dynamically active aquifers of the Po River Basin, Italy

Abstract: Abstract. Uncoupling between the flow field and the stress field in pumped aquifers is the basis of the classical groundwater hydrology. Recently, some authors have disputed the assumption of uncoupling with regard to both fluid dynamics and porous medium deformation. The issue is very important as it could undermine the traditional approach to simulate subsurface flow, analyze pumping tests, and predict land subsidence caused by fluid withdrawal. The present paper addresses the problem of coupling versus unco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(72 citation statements)
references
References 37 publications
0
72
0
Order By: Relevance
“…The process is theoretically described by the 3-D fully coupled poroelasticity model originally developed by Biot [1941]. Gambolati et al [2000] and Settari et al [2005] have shown that in the reservoirs and aquifers of the Po River basin coupling between the flow and the stress fields is weak and uncoupling, as is usually assumed by hydrogeologists and petroleum engineers, is fully warranted on any timescale of practical interest.…”
Section: Methodsmentioning
confidence: 99%
“…The process is theoretically described by the 3-D fully coupled poroelasticity model originally developed by Biot [1941]. Gambolati et al [2000] and Settari et al [2005] have shown that in the reservoirs and aquifers of the Po River basin coupling between the flow and the stress fields is weak and uncoupling, as is usually assumed by hydrogeologists and petroleum engineers, is fully warranted on any timescale of practical interest.…”
Section: Methodsmentioning
confidence: 99%
“…In geomechanical investigations at regional scale, uncoupled pressure -displacements solution can be safely used in predicting land subsidence in compacting sedimentary on any time scale of practical interest (Gambolati et al, 2000;Teatini et al, 2006Teatini et al, , 2010. In this study, an uncoupled approach is thus followed, with the flow field initially computed at each time step and the deformation then calculated using the pore pressure gradient as a known source of strength in the geomechanical model.…”
Section: Model Setupmentioning
confidence: 99%
“…Uncoupling the flow field from the stress field is a usual assumption in groundwater hydrology. Gambolati et al (2000) have shown that uncoupling has generally no measurable influence over any timescale of practical interest. Hence, in the present analysis a 1-way coupled approach is followed where the pore pressure variation is first simulated by a 3-D groundwater flow model, and then the land settlement is predicted by a 3-D geomechanical model with the pore pressure change used as an external distributed source of strength.…”
Section: Mathematical Modelmentioning
confidence: 99%